Contested Meanings of Hate Speech and the Post-Truth Condition on Digital Platforms - Kaarina Nikunen; Paula Haara; Heidi Kosonen; Aleksi Knuutila; Reeta Pöyhtäri; Tuija Saresma (Social Media + Society)
In the everyday context, the term “hate speech” has become increasingly politicized and emotionally charged, yet these vernacular constructions of hate speech remain under-explored. Used as both a rhetorical weapon and an object of genuine concern, various understandings of hate speech circulate within interactive everyday cultures of digital media, shaped by the digitalised media environment. With the combination of computational and qualititative research methods, this article explores the struggle over meanings of hate speech. From a large dataset of 289,933 messages, we identified the 10 most relevant themes. We further used articulation theory to analyze different political and social articulations of hate speech. We situate these articulations to the context of post-truth condition, characterized with crisis of trust and truth-telling. Our study identified articulations of confusion, uncertainty, ridicule, trivialization, and censorship in the context of hate speech. The results show that the struggle over the power to define hate speech simultaneously involves a struggle to overturn the definitional power of research institutions and official and knowledge authorities. Overall, the study contributes to the research on hate speech by showing the vernacular, contextual and localized nature of hate speech that emerges in reference to particular political actors, events and debates. Furthermore, the study illustrates the societal importance of the hate speech debate and the ways in which the concept itself, through multiple articulations, is used as tool in the post-truth battle to impede and disturb democratic debate and to serve particular political ends.